2015
DOI: 10.1179/2047773215y.0000000034
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of parasiticLegionellain surface waters by using immunomagnetic separation and amoebae enrichment

Abstract: Free-living amoebae (FLA) are potential reservoirs of Legionella in aquatic environments. However, the parasitic relationship between various Legionella and amoebae remains unclear. In this study, surface water samples were gathered from two rivers for evaluating parasitic Legionella. Warmer water temperature is critical to the existence of Legionella. This result suggests that amoebae may be helpful in maintaining Legionella in natural environments because warmer temperatures could enhance parasitisation of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In its aquatic habitats L. pneumophila replicates intracellularly in various free-living protozoa, including amoebae such as Acanthamoeba, Vermamoeba (formerly Hartmannella ), Naegleria, Echinamoeba , and Vahlkampfia , as well as in ciliates like Tetrahymena (Fields, 1996 ; Greub and Raoult, 2004 ; Hilbi et al, 2011 ; Hsu et al, 2015 ). From an evolutionary point of view, interactions of L. pneumophila with protozoa shaped the relationship and likely led to adaptive responses, which enable the pathogen to also infect mammalian phagocytes such as human alveolar macrophages (Greub and Raoult, 2004 ; Molmeret et al, 2005 ; Jäger et al, 2014 ).…”
Section: Protozoa As Environmental Niches Of Legionella mentioning
confidence: 99%
See 1 more Smart Citation
“…In its aquatic habitats L. pneumophila replicates intracellularly in various free-living protozoa, including amoebae such as Acanthamoeba, Vermamoeba (formerly Hartmannella ), Naegleria, Echinamoeba , and Vahlkampfia , as well as in ciliates like Tetrahymena (Fields, 1996 ; Greub and Raoult, 2004 ; Hilbi et al, 2011 ; Hsu et al, 2015 ). From an evolutionary point of view, interactions of L. pneumophila with protozoa shaped the relationship and likely led to adaptive responses, which enable the pathogen to also infect mammalian phagocytes such as human alveolar macrophages (Greub and Raoult, 2004 ; Molmeret et al, 2005 ; Jäger et al, 2014 ).…”
Section: Protozoa As Environmental Niches Of Legionella mentioning
confidence: 99%
“…A number of studies indicated that L. pneumophila is highly adapted and manages to infect a wide range of protozoan and metazoan hosts (Hilbi et al, 2011 ; Bergmann and Steinert, 2015 ; Hsu et al, 2015 ). This suggests that many protozoan host species and other interaction partners of L. pneumophila in the environment remain to be discovered.…”
Section: Protozoa As Environmental Niches Of Legionella mentioning
confidence: 99%
“…Legionellae are gram-negative bacteria commonly found in freshwater ecosystems such as rivers, lakes, ponds, and streams [1,2]. The entry of bacteria into purpose-built water systems and drinking-water distribution systems make a serious health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Immunomagnetic separation has been successfully adopted for identifying Legionella pneumophila serogroup 1 from tap water and other environmental samples as well as other microorganisms from clinical samples and foods (10)(11)(12)(13)(14)(15). We thought that isolation rates may be improved by eliminating the acid wash step and using decontamination with glycine, vancomycin hydrochloride, polymyxin B sulfate, and cycloheximide (GVPC) together with immunomagnetic separation.…”
mentioning
confidence: 99%